Quality Attributes and Metabolic Profiles of Uvaia (Eugenia pyriformis), a Native Brazilian Atlantic Forest Fruit - Spricigo, Poliana Cristina [UNESP]; Almeida, Luísa Souza; Ribeiro, Gabriel Henrique; Correia, Banny Silva Barbosa; Taver, Isabela Barroso; Jacomino, Angelo Pedro; Colnago, Luiz Alberto (MDPI, 2023)
The uvaia is a native Brazilian Atlantic Forest Myrtaceae fruit with a soft pulp, ranging from yellow to orange, with a sweet acidic flavor and sweet fruity aroma. Uvaias present consumption potential, but their physicochemical characteristics are still understudied. In this context, we describe herein the metabolites of uvaia that have been determined by nuclear magnetic resonance spectroscopy. We screened 41 accessions and selected 10 accessions based on their diversity of physicochemical attributes, i.e., their fresh mass, height, diameter, yield, seed mass, total soluble solids, and titratable acidity. Twenty-six metabolites were identified, including sugars, acids, and amino acids. The results of this study comprise the most complete report on sugars and acids in uvaias. The relevant metabolites in terms of abundance were the reducing sugars glucose and fructose, as well as malic and citric acids. Furthermore, this study represents the first description of the uvaia amino acid profile and an outline of its metabolic pathways. Uvaia quality attributes differ among accessions, demonstrating high variability, diversity, and several possibilities in different economic areas. Our findings may help in future breeding programs in the selection of plant material for industries such as food and pharmaceuticals.
Keywords: Eugenia pyriformis; nuclear magnetic resonance; postharvest